Diversity and Composition of Insect Species Associated with Natural Rattan Habitats in Namo Village, Kulawi, Central Sulawesi - Musdalifah Nurdin; Samsurizal M Suleman; Syech Zainal; Moh Sabran; Raya Agni; Manap Trianto (Biology, Medicine, & Natural Product Chemistry, 2025)
Tropical forest ecosystems are home to diverse insect communities that play essential ecological roles, including pollination, decomposition, and nutrient cycling. Among the key forest plants, rattan (Arecaceae) provides both ecological and economic benefits and serves as an important microhabitat for various insect species. This study aimed to identify and analyze the diversity of insect species associated with natural rattan habitats in Namo Village, Kulawi District, Central Sulawesi, Indonesia. Insect sampling was carried out using sweep nets, pitfall traps, and yellow pan traps along rattan-dominated forest transects. A total of 125 individual insects were collected, representing 7 orders, 28 families, and 37 species. The order Hymenoptera showed the highest abundance (41.6%), dominated by Formicidae and Apidae families, followed by Coleoptera (25.6%) and Diptera (17.6%). The Shannon–Wiener Diversity Index (H’ = 2.84) indicated moderate species diversity with high evenness (E = 0.83). Functionally, the insect community consisted of pollinators (38.2%), herbivores (25.4%), decomposers (19.6%), and predators (16.8%). These findings demonstrate that natural rattan ecosystems support diverse and functionally balanced insect assemblages, reflecting stable ecological conditions and minimal anthropogenic disturbance. Conserving natural rattan stands is therefore crucial for maintaining biodiversity and sustaining ecological functions such as pollination and decomposition within tropical forest ecosystems.